Penelitian hadits tentang larangan menikah dengan saudara sesusuan - Putri, Ahlam Dita (Maliki Interdisciplinary Journal, 2024)
Hadith is a source of Islamic law other than the Qur'an which originates from the Prophet's words, the Prophet's behavior, or even the Prophet's silence. To obtain the truth of a hadith, a process of assessing everything related to the hadith is required. Like the assessment of the hadith narrators. In the hadith narrated by Imam Ahmad regarding the prohibition of marrying half-brothers, more in-depth research can be carried out regarding how the marriage partners behave. Sourced from the verses of the Qur'an and the hadith, a legal ijtihad emerged regarding the prohibition of marrying a blood relative along with all the terms and conditions which were then used as the legal basis for every Muslim.